Decoding the new Taliban : insights from the Afghan field - Giustozzi, Antonio (London : Hurst & Co., 2009)
"Decoding the new Taliban includes a number of detailed studies of specific regions or provinces, which for different reasons are especially significant for the Taliban and for understanding their expansion. Alongside these regional studies, the volume includes thematic analyses of negotiating with the Taliban, the Taliban's propaganda effort and it's strategic vision." -- BOOK JACKET
Includes bibliographical references and index.
Keywords: Taliban; Terrorists -- Afghanistan; Religious militants -- Afghanistan